Wood behavior at high temperatures - Figueroa, Manuel Jesús Manriquez (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2009)
In Brazil, the combustibility of wood and insecurity regarding potential fire risks are considered restrictions for the use of timber-structured buildings. This situation is due to the lack of knowledge about the behavior of wood structures on fire. The aim of this study is to present a comprehensive literature review on the behavior of wood at high temperatures, discussing issues related to thermal degradation, charring rate and the influence of temperature on the mechanical properties of wood. This information may contribute to improve numerical models on the thermo-mechanical behavior of wood structures on fire, in order to build safer wooden buildings and also to eliminate preconceptions regarding the use of this material.